The level of Collaborative Knowledge Creation According to the Principles of the Trialogical Learning Approach and its Impact on the Teaching Performance in Oman - Al-Hajari, Fatemah; Ambusaidi, Abdullah (Jordan Journal of Educational Sciences, 2019)
The purpose of this study is to determine the level of collaborative knowledge creation among Omani science teachers, and the impact of this level on their teaching performance. The study community consisted of (111) teachers enrolled in a professional development program entitled "Science Experts" presented by Specialist Center for Professional Training of Teachers. The study sample included (43) teachers; each of them wrote a case study report, in which they identified a problem, and the professional practices they have followed to solve those problems. The study used analysis descriptive research method. Artifacts analysis rubric was designed to analyze the content of the teachers’ case studies’ reports, consisting of (18) items, divided according to the designing principles of the trialogical learning approach. The results of the study showed that the average level of collaborative knowledge creation in the study sample was (1.89) with percentage of (63%), which is classified as "medium". The principle of "Emphasizing development and creativity on shared objects through transformations and reflection" achieved the most indicators of collaborative knowledge creation, followed by the fifth principle "Promoting cross-fertilization of various knowledge practices and artifacts across communities and institutions". In addition, the results also showed that the level of collaborative knowledge creation among Omani science teachers influences their performance in teaching science, and it can be used to distinguish between high- and low- teaching performance in teaching science. The results of the study showed that the high level of "raising awareness of the problem and its causes" indicates high teaching performance rate of science teachers.